2014
DOI: 10.15171/ijhpm.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Technical Efficiency of Health Systems: A Case Study of Economic Cooperation Organization (ECO) Countries (2004–10)

Abstract: In order to maximize the TE of health systems, health policy-makers should pay special attention to the proper use of healthcare resources according to the people's needs, the appropriate management of the health system resources, allocating adequate budgets to the health sector, establishing an appropriate referral system to provide better public access to health services according to their income and needs, among many others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
(30 reference statements)
2
30
1
2
Order By: Relevance
“…Following these results, it can be concluded that physical resources had less influence on organisation efficiency of Mbeya UWSA. These findings are in line with Ravangard et al (2014) who found that the efficiency of many organizations are affected by limited physical resources required to undertake specific tasks. It was also discovered that 70% of physical resources used were old and needed replacement and there was a shortage and 40% of them were not of good quality and outdated to cater for the high growing customers' demands of customers as fairly few customers were connected to the central system.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Following these results, it can be concluded that physical resources had less influence on organisation efficiency of Mbeya UWSA. These findings are in line with Ravangard et al (2014) who found that the efficiency of many organizations are affected by limited physical resources required to undertake specific tasks. It was also discovered that 70% of physical resources used were old and needed replacement and there was a shortage and 40% of them were not of good quality and outdated to cater for the high growing customers' demands of customers as fairly few customers were connected to the central system.…”
Section: Resultssupporting
confidence: 91%
“…Availability of modern facilities for water supply (2.50), office equipments (2.59) and modern equipments (2.57) contributes to a small extent to organisation efficiency with mean score slightly equal to cut-off point. In order to enhance efficiency of the utility, the utility should procure modern physical resources such as computers, pipes, motors and other technical equipments (Ravangard et al, 2014). In similar vein, the utility should provide on the job training to employees in order to equip them with relevant skills on how to use such equipments to achieve the desired output.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the hospital's operating costs and lack of sufficient efficiency of healthcare system raise questions on the way of resources consuming by the hospital . When issues related to capital and labor force supply are compounded by the lack of full utilization of existing tools and equipment that is caused by working practices in undeveloped and developing countries, the efficiency rate decreases and it creates a kind of capital and labor force waste in times of scarcity . Therefore, health promotion is an economic and social subject as well as ethical duty, and any type of health service planning should be considered as a part of the health policy approach …”
Section: Introductionmentioning
confidence: 99%
“…Use the limited resources efficiently and spend public funds on the suitable and effective services, as well as. Identification of these factors is a method for accurate estimation of health resources (1,2) and macroeconomic policymaking in the health sector (3). In fact, research on the utilization of health services helps identify factors, which facilitate or prevent access to these services (4).…”
Section: Introductionmentioning
confidence: 99%